Novel method exploration of monitoring neutron beam using Cherenkov photons in BNCT. (March 2019) - Shu, Diyun; Tang, Xiaobin; Geng, Changran; Zhang, Xudong; Gong, Chunhui; Shao, Wencheng; Liu, Yuanhao
Abstract: Ensuring the stability of the neutron beam during boron neutron capture therapy (BNCT) is essential. The goal of this work was to explore a novel method using Cherenkov photons for real-time monitoring of neutron beam in BNCT. The Monte Carlo toolkit Geant4, was used to calculate the Cherenkov photons and dose based on a cubic phantom and Chinese hybrid radiation phantom under different conditions. Based on the study on the cubic phantom, the change of neutron beam characteristics indeed have an impact on dose, which needs quality assurance. The relationship between Cherenkov photons and gamma dose was favorable. The maximum relative variation of the generation of Cherenkov photons is approximately 3.51%, even when the relative change of boron concentration reaching 60%. However, comparing the results of the neutron beam with the original characteristics, the maximum relative variation of Cherenkov photons reaches 14.75% and 14.68% for the usage of Neuboron- spectrum and 5-degree rotation of neutron beam field orientation, respectively. Therefore, the intensity and distribution of Cherenkov photons can only be observably changed by neutron beam characteristics. Based on the Chinese hybrid radiation phantom, the changes in the intensity and distribution of Cherenkov photons can also be observed inside the phantom, and these changes are evident by a detector outside the phantom. Thus, Cherenkov photons has the potential application for neutron beam monitoring. Highlights: Method of monitoring neutron beam using Cherenkov photons in BNCT was explored. Chinese hybrid radiation phantom was used to investigate this novel method. Response relation between Cherenkov photons and gamma dose was observed in BNCT. Cherenkov photons can only be observably changed by neutron beam characteristics.